Robotic hysterectomy versus conventional laparoscopic hysterectomy: Outcome and cost analyses of a matched case–control study - Sarlos, Dimitri; Kots, LaVonne; Stevanovic, Nebojsa; Schaer, Gabriel (European journal of obstetrics & gynecology and reproductive biology, 2010)
Robotic surgery, with its technical advances, promises to open a new window to minimally invasive surgery in gynaecology. Feasibility and safety of this surgical innovation have been demonstrated in several studies, and now a critical analysis of these new developments regarding outcome and costs is in place. So far only a few studies compare robotic with conventional laparoscopic surgery in gynaecology. Our objective was to evaluate our initial experience performing total robot-assisted hysterectomy with the da Vinci ® surgical system and compare peri-operative outcome and costs with total laparoscopic hysterectomy. For this prospective matched case–control study at our institution, peri-operative data from our first 40 consecutive total robot-assisted hysterectomies for benign indications were recorded and matched 1:1 with total laparoscopic hysterectomies according to age, BMI and uterus weight. Surgical costs were calculated for both procedures. Surgeons’ subjective impressions of robotics were evaluated with a self-developed questionnaire. No conversions to laparotomy or severe peri-operative complications occurred. Mean operating time was 109 (113; 50–170) min for the robotic group and 83 (80; 55–165) min for the conventional laparoscopic group. Mean postoperative hospitalisation for robotic surgery was 3.3 (3; 2–6) days versus 3.9 (4; 2–7) days for the conventional laparoscopic group. Average surgical cost of a robot-assisted laparoscopic hysterectomy was €4067 compared to €2151 for the conventional laparoscopic procedure at our institution. For the robotic group wider range of motion of the instruments and better ergonomics were considered to be an advantage, and lack of direct access to the patient was stated as a disadvantage. Robot-assited hysterectomy is a feasible and interesting new technique with comparable outcome to total laparoscopic hysterectomy. Operating times of total laparoscopic hysterectomy seem to be achieved quickly especially for experienced laparoscopic surgeons. However, costs of robotic surgery are still higher than for conventional laparoscopy. Randomised clinical trials need to be conducted to further evaluate benefits of this new technology for patients and surgeons and analyse its cost-effectiveness in gynaecology.